ECOLOGICAL STUDY: PREVALENCE OF CHRONIC ENERGY DEFICIENCY AMONG PREGNANT WOMEN IN NUSA TENGGARA PROVINCES, INDONESIA - Selamet, Muhammad Aji Sukmo; Megatsari, Hario; Hairi, Farizah Mohd (Journal of Public Health Research and Community Health Development, 2024)
Background: Pregnant women who experience Chronic Energy Deficiency (CED) will be at risk of decreased muscle strength which will be used in the process of childbirth resulting in the occurrence of various complications such as low birth weight babies, miscarriage, birth defects, premature, and even infant death. The problem of CED among pregnant women requires intervention not only in nutritional aspects but also in socio-economic aspects. Purpose: This study aimed to determine the overview of the chronic energy deficiency among pregnant women in Nusa Tenggara in 2018 and the factors that influence it. Methods: The approach used in this study was ecological analysis methods. All districts and cities in West Nusa Tenggara and East Nusa Tenggara were included in this study. This study looked at the prevalence of CED among pregnant women and 4 other independent variables, namely the percentage of supplementary feeding, the percentage of added blood tablets, poverty rate, and literacy rate. The data were analyzed using cross-tabulation. Results: The results show that supplementary feeding and literacy rates do not affect the incidence of CED. However, other variables such as the provision of blood booster supplements and poverty rate affect the incidence of CED. Conclusion: Health care facilities need to improve services and counseling regarding the importance of nutrition during pregnancy and the need for government support in improving the socio-economic status of the community to reduce the prevalence of CED in Nusa Tenggara.